Time spent in different sedentary activity domains across adolescence: a follow-up study - Michael Pereira da Silva; Roseane de Fátima Guimarães; Eliane Denise Araújo Bacil; Thiago Silva Piola; Edmar Roberto Fantinelli; Fabio Eduardo Fontana; Wagner de Campos (Elsevier, 2022)
Objective: This longitudinal study aimed to verify possible changes in the time spent in sedentary activities occurring as screen-time, educational, cultural, social, and transportation domains in a sample of Brazilian adolescents between 2015 and 2017. Methods: It is a longitudinal prospective study with 586 adolescents from 12 to 15 years old at the Baseline (2015) enrolled in 14 public schools from Curitiba, Brazil. The Adolescent Sedentary Activity Questionnaire assessed the time spent in sedentary activities in five domains (recreational screen-time, educational, cultural, social, and transportation). A series of linear random effects regressions analyzed changes in the sedentary time between 2015 and 2017, with p < .05. Results: Overall, 323 adolescents dropped out of the study resulting in a retention rate of 44.9%. The overall sedentary time remained stable from 2015 to 2017 (-3.98 min/day, 95%CI: -15.39; 7.42). The screen-time decreased (-22.22 min/day, 95%CI: -30.30; -14.15), and educational (8.29 min/day, 95% CI: 3.52; 13.06), cultural (3.41 min/day, 95% CI: 0.66; 6.15) and social sedentary activities (8.20 min/day, 95% CI: 2.06; 14.34) increased from 2015 to 2017. Conclusion: Significant reductions in screen-time were evidenced along with increases in time spent on other sedentary activities of educational, cultural, and social nature. KeywordsSedentary behavior, Adolescent health, Longitudinal studies